Empower your research with TRANSPORT! 30 years together - Prentkovskis, Olegas; Junevičius, Raimundas; Baublys, Adolfas (Transport, 2015)
"Empower your research with TRANSPORT! 30 years together." Transport, 30(4), pp. 383–384